Gaza Weddings : a Novel. - Nasrallah, Ibrahim (Hoopoe Fiction., 2017)
Twin sisters Randa and Lamis live in the besieged Gaza Strip. Inseparable to the point that even their mother cannot tell them apart, they grow up surrounded by the random carnage that characterizes life under occupation. Randa, who wants to be a journalist, writes to record the devastation around her, taking pictures of martyred children. Meanwhile, their beloved neighbor Amna quietly converses with all those she has lost, as she plans the wedding of Lamis and her son Saleh. With their menfolk almost entirely absent, it is the women who take center stage in this poignant novel of resilience,